Increased EZH2 Levels in Anterior Cingulate Cortex Microglia Aggravate Neuropathic Pain by Inhibiting Autophagy Following Brachial Plexus Avulsion in Rats - Meng, Xiang-Lei (Neurosci Bull, 2020)
After brachial plexus avulsion (BPA), microglia induce inflammation, initiating and maintaining neuropathic pain. EZH2 (enhancer of zeste homolog 2) has been implicated in inflammation and neuropathic pain, but the mechanisms by which it regulates neuropathic pain remain unclear. Here, we found that EZH2 levels were markedly upregulated during BPA-induced neuropathic pain in vivo and in vitro, stimulating pro-inflammatory cytokines (IL-1β, TNF-α, and IL-6) secretion in vivo. In rats with BPA-induced neuropathic pain, mechanical and cold hypersensitivities were induced by EZH2 upregulation and inhibited by EZH2 downregulation in the anterior cingulate cortex. Microglial autophagy was also significantly inhibited, with EZH2 inhibition activating autophagy and reducing neuroinflammation in vivo. However, this effect was impaired by inhibiting autophagy with 3-methyladenine, suggesting that the MTOR signaling pathway is a functional target of EZH2. These data suggest that EZH2 regulates neuroinflammation and neuropathic pain via a novel MTOR-mediated autophagy signaling pathway, providing a promising approach for managing neuropathic pain. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12264-020-00502-w) contains supplementary material, which is available to authorized users.